Prince Caspian : the return to Narnia - Lewis, C. S. (Clive Staples), 1898-1963 (Lewis, C. S. (Clive Staples), 1898-1963. Chronicles of Narnia, 1994)
Four children help Prince Caspian and his army of Talking Beasts to free Narnia from evil.